Recent advances in bioprinting technologies for engineering different cartilage-based tissues - Agarwal T.; Chiesa I.; Presutti D.; Irawan V.; Vajanthri K.Y.; Costantini M.; Nakagawa Y.; Tan S.-A.; Makvandi P.; Zare E.N.; Sharifi E.; De Maria C.; Ikoma T.; Maiti T.K. (My University, 2025)
Inadequate self-repair and regenerative efficiency of the cartilage tissues has motivated the researchers to devise advanced and effective strategies to resolve this issue. Introduction of bioprinting to tissue engineering has paved the way for fabricating complex biomimetic engineered constructs. In this context, the current review gears off with the discussion of standard and advanced 3D/4D printing technologies and their implications for the repair of different cartilage tissues, namely, articular, meniscal, nasoseptal, auricular, costal, and tracheal cartilage. The review is then directed towards highlighting the current stem cell opportunities. On a concluding note, associated critical issues and prospects for future developments, particularly in this sphere of personalized medicines have been discussed. © 2021 Elsevier B.V.